2019
DOI: 10.1002/mc.23009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence supporting the precursor nature of atypical adenomatous hyperplasia of the prostate

Abstract: Atypical adenomatous hyperplasia (AAH) of the prostate is characterized by lobular proliferation of closely packed small acini. It is hypothesized that AAH is a precursor lesion for low‐grade prostate cancer arising from the transition zone. Telomere dysfunction is common during malignant transformation of epithelia. In this study, we investigate telomere shortening in AAH (n = 93), high‐grade prostatic intraepithelial neoplasia (HGPIN) ( n = 68), and prostatic adenocarcinoma (PCA) ( n = 70) using quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…TLs of these lesions differed significantly when compared with one another and the normal tissue (P<0.001). These findings, along with AMACR expression, suggest the premalignant nature of AAH and its role in prostate cancer development (71). Lastly, TL in BPH is associated with race, as African American males have been shown to exhibit significantly shorter telomeres compared to Caucasian males; longer telomeres have also been found to be associated with an increased risk of cancer (72).…”
Section: Telomeres and Telomerase Across Pre-neoplastic Lesionsmentioning
confidence: 88%
See 1 more Smart Citation
“…TLs of these lesions differed significantly when compared with one another and the normal tissue (P<0.001). These findings, along with AMACR expression, suggest the premalignant nature of AAH and its role in prostate cancer development (71). Lastly, TL in BPH is associated with race, as African American males have been shown to exhibit significantly shorter telomeres compared to Caucasian males; longer telomeres have also been found to be associated with an increased risk of cancer (72).…”
Section: Telomeres and Telomerase Across Pre-neoplastic Lesionsmentioning
confidence: 88%
“…This characteristic is also shared by PIN, but not by BPH, as Southern blot analysis has revealed that normal epithelium and BPH have similar average TLs (6.6 and 6.4 kb, respectively) (70). Using Q-FISH assay, Cheng et al (71) compared TLs between normal epithelium, AAH, high-grade PIN and prostatic adenocarcinoma (PCA). Shortened telomeres were present in 20% of AAH, 68% of high-grade PIN and 83% of PCA samples.…”
Section: Telomeres and Telomerase Across Pre-neoplastic Lesionsmentioning
confidence: 99%
“…Two hotspot mutations occur at the proximal region of the TERT promoter (−124 and −146 bp from the ATG) with a cytidine-tothymidine (C>T) dipyrimidine transition, which are called as C228T (-124C>T) and C250T (-146C>T), respectively (31,32). Across UC subtypes, the frequency of TERT promoter mutations is different, varying from less than 20% in UCU, 45% in UCRPs, to ~85% in UCBs (28,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49). The C228T mutation is predominant and the presence of C228T and C250T is mutually exclusive, indicating a functional redundancy of these two mutations (Figure 2).…”
Section: The Activating Tert Promoter Mutation In Ucsmentioning
confidence: 99%
“…AAH can be difficult to distinguish from low-grade prostatic adenocarcinoma. Very few clinical follow-up studies, even when based on image analysis and molecular investigation, 10,11 have linked this disorder to PCa. Such a link might be difficult to establish if only a small subset of AAH has a premalignant potential.…”
Section: Pin Without Morphologic Changes and Atypical Adenomatous Hyp...mentioning
confidence: 99%